THE USE OF GEOLOGICAL STRENGTH INDEX GSI. RECOMMENDATIONS, LIMITATIONS AND RANGES OF VALUES IN MOST COMMON ROCK TYPES - Μαρίνος, Β.; Μαρίνος, Π.; Hoek, E. (Bulletin of the Geological Society of Greece, 2004)
After one decade of application of the Geological Strength Index, GSI, and its extensions, in the quantitative characterisation of the rock mass, the present paper attempts to answer the questions that have been raised by the users about the determination of the GSI for various qualities of rock masses and various conditions. Recommendations are given and cases are discussed where GSI is not applicable. The paper also gives general guidance on the field of GSI values of rock masses for the most common rock types based on their pétrographie and their most usual structural characteristics.